Development of observing dolphin population method using Small Vertical Take-off and Landing (VTOL) Unmanned Aerial System (AUV). (May 2019) - Subhan, B; Arafat, D; Santoso, P; Pahlevi, K; Prabowo, B; Taufik, M; Kusumo, B S; Awak, K; Khaerudi, D; Ohoiulun, H; Nasetion, F I; Madduppa, H
Abstract: Indonesia has a very high diversity of Cetacean, observation with good accuracy and precision must be a priority in every observation. Several methods have been developed to help calculate the marine mammal population, one of them by using Vertical Take-off and Landing (VTOL) Unmanned Aerial System (UAS). VTOL UAS is flown at a certain height to capture photos that contain the number of individuals in a pod, while also mapping the movements and recording their behaviors. The aim of this study was to determine the ideal angle to capture the photos. Several observation angles, 30°, 60°, and 90° were tested Observations were conducted in three sites in Indonesia (Sepa Island, Thousand Islands, Kepulauan Seribu National Park (TNKS); Liang Beach, Maluku Island; and Nai Island Kei Achipelago). The results showed that the angles greatly affected the number of objects in the photograph. For example, on the Island of Sepa, at the angle 30°, 60°, and 90°, the number of dolphins obtained were 3, 9 and 14, respectively. This study did not find any object rejection during observation with VTOL UAS. This study suggests that higher angle of photograph from VTOL UAS increases the accuracy of the observation of marine mammals.